2021
DOI: 10.1016/j.fochx.2021.100165
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of cholesterol esterase and lipase inhibitory peptides from amaranth protein hydrolysates

Abstract: Highlights Gastric, microbial and plant-based enzymes were used to produce Amaranth protein hydrolysates (APHs). APHs displayed enhanced cholesterol esterase (CEase) and pancreatic lipase (PL) inhibitory activities. Bromelain generated hydrolysates showed the highest CEase and PL inhibitory activity. FPFPPTLGY, FGAPR, and FPFVPAPT were predicted as potential PL inhibitors and FPFVPAPT as CEase inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…D–2 showed more effective inhibition, and its inhibitory effect on CE increased as its concentration increased, with an IC50 value of 3.19 mg/mL (2.62 mM) ( Figure 6 b). Peptides with pancreatic CE inhibitory activity were obtained and predicted from camel milk and amaranth protein [ 2 , 19 , 51 ]. To date, no study has investigated the CE inhibitory activity of loach peptides in in vitro studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…D–2 showed more effective inhibition, and its inhibitory effect on CE increased as its concentration increased, with an IC50 value of 3.19 mg/mL (2.62 mM) ( Figure 6 b). Peptides with pancreatic CE inhibitory activity were obtained and predicted from camel milk and amaranth protein [ 2 , 19 , 51 ]. To date, no study has investigated the CE inhibitory activity of loach peptides in in vitro studies.…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant compounds are important for human health as they prevent or reduce excessive free radicals and reactive oxygen species (ROS) produced by the body, thus reducing damage to DNA, proteins, and lipids [ 1 , 2 , 3 ]. Antioxidants and enzyme inhibitors are employed as part of the control strategy for the management of healthy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, numerous studies have demonstrated the potential of anti-hypercholesterolemic peptides derived using specific enzymes (alcalase, pepsin, trypsin, flavourzyme, chymotrypsin, etc.) in inhibiting CEase and PL active sites [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work suggests that first and foremost peptides and protein hydrolysates derived from these beneficial species for the human health are worth considering [ 1 ]. The first study on an amaranth protein deriving bioactive peptide with cholesterol esterase and pancreatic lipase inhibitory activities was published in 2021 by Ajayi and colleagues [ 2 ].…”
Section: Introductionmentioning
confidence: 99%